1998
DOI: 10.1038/sj.bdj.4809870
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the impression tray on the accuracy of impressions for crown and bridge work--an investigation and review

Abstract: Metal and rigid plastic stock trays give greater accuracy in the putty/wash silicone twin mix impression technique compared with flexible plastic ones for crown and bridge work. Those using the latter should be aware of their shortcoming in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 0 publications
1
32
0
2
Order By: Relevance
“…Both the techniques were found to be accurate and not significantly different from each other 22 . In most of the studies reported in literature so far, precision measurement was done using instruments such as travelling microscope, 23,16 micrometer, 24 vernier caliper, 25 and laser probes. In the present study, a travelling microscope (ELFO, INDIA) was used.…”
Section: Discussionmentioning
confidence: 99%
“…Both the techniques were found to be accurate and not significantly different from each other 22 . In most of the studies reported in literature so far, precision measurement was done using instruments such as travelling microscope, 23,16 micrometer, 24 vernier caliper, 25 and laser probes. In the present study, a travelling microscope (ELFO, INDIA) was used.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of a metal or rigid tray allows for greater accuracy. 2 What typically happens (see Fig. la,b) is the putty tends to push the light body wash off the prepared tooth.…”
Section: Q Which Impression Technique Should I Consider?mentioning
confidence: 99%
“…[13][14][15] Rigid metal trays however can minimise such distortions and are to be recommended for putty-wash impressions.…”
Section: The Problems Of Putty-washmentioning
confidence: 99%